Kilka uwag o realizmie filmowym i jego społecznym wymiarze - Śliwińska, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
This text explores the concept of realism in the context of cinema on various levels. It examines the relationship between film and reality, compares realism with classic narration and art film, explores film techniques that aim to authentically depict reality on screen, and considers the social aspect of realism. Regarding the latter term, an attempt is made to identify the characteristics that best capture its essence. The text aims to present different contexts related to the concept of realism, but it does not provide a comprehensive and in-depth analysis of this phenomenon.